Life cycle based decision support for sustainable automotive engineering and energy planning - Li, Xiang (2017)
Automotive industry is one of the most influential industries globally, however, nowadays it has encountered critical environmental challenges. Vehicles operation has caused dramatic global energy use and greenhouse gas emissions. The continuous market growth in the future will lead to increased significance on the issue of sustainable development for automotive markets. Many innovations and sustainable approaches have been applied in tackling the polluting problems, such as new light-weight materials, new power configuration, and better waste treatment technologies. It is necessary to build a better understanding on the decision-making processes associated with automotive engineering and energy planning. However, there is lack of multi-objective optimisation models for product design and recycling and lack of proper cost modelling in energy transition towards more sustainable energy mix. This thesis firstly conducts a sustainability analyse of an automotive power seat as an empirical study. The quantitative technique is based on the life cycle assessment, aiming to identify environmental impacts through lifetime span including raw material extraction, upstreaming energy production, product manufacturing, and car usage and end life vehicle treatment. Toward this aim, a serial of major environmental indicators and energy consumption is generated. The proposal life cycle assessment model focuses on multi-tier supply chains of the automotive industry. This model re-organises relevant activities to make the quantification of LCA indicators more feasible. Several potential weight reduction approaches have been analysed in the following empirical study that show the benefits of power seats applied in light weighting material aluminium and magnesium. The model will assist researchers in better understanding the overall environmental impacts related to automotive parts design. This thesis also studies the waste treatment of automotive components as one of the key processes among the full life cycle assessment. Composites materials such as carbon fibre reinforcement polymer are promising light weight material for future car production. Recovering value from composites waste can help to address the high cost and environmental burden of producing carbon fibres. Life cycle costing and environmental assessment methods are applied in this study to quantify the financial and environmental impacts of alternative waste treatment routes, comparing landfilling; incineration with energy recovery; and mechanical recycling. Our experimental results show that, in the absence of regulation, landfill represents the least-cost CFRP waste treatment of those considered. When Landfill Tax legislation is included in the analysis, incineration becomes the preferred option from a cost perspective. However, incineration is associated with high greenhouse gas emissions. Mechanical recycling and fibre reuse to displace virgin glass fibre can provide the greatest GHG emissions reductions of the treatment routes considered, provided residual recyclates are landfilled rather than incinerated. Energy is a core factor in any LCA studies and the industry is under pressure to increase clean energy production. However, very little research has been done in optimizing the transition process from the traditional coal-fired power generation to other clean energy production systems. This thesis develops an optimization model to improve eco-efficiency based on life cycle environmental/cost assessment that can examine the associated impacts and strategies on emerging techniques. The model applied a multi-objective optimization coupled with a goal programming approach to identify the optimal automotive upstream energy mix when emerging sustainable power capacity becomes available. Based on our developed model, a hypothetical coal power plant has been investigated to determine the phase out strategies according to the trade-off among several environmental impacts, financial cost and policy goals for emissions reduction. Retrofitting to biomass power and displacing to natural gas power, for the first time, are analysed and compared to improve the environmental performance of existing coal fired electricity. This thesis helps fill the gap in terms of holistic approach towards the improvement of environmental and financial performances on automotive parts and its associated waste management and energy. Those outcomes are valuable for automotive industry, government, and other stakeholders to optimize strategical decisions on sustainable development that can assist the future vehicle design, the development of policies and energy planning.